MARKETING MIX STRATEGY IN ATTRACTING PROSPECTIVE HAJJ AND UMRAH PILGRIMS AT PT. RIZQUNA MEKKAH MADINAH - Muh. Nur Iman; Seny Luhriyani Sunusi; Himala Praptami Adys (Bahasa Inggris Program Sarjana Terapan, Universitas Negeri Makassar, 2026)
This study aims to examine the application of marketing mix strategies covering product, price, place, and promotion aspects in attracting prospective Hajj and Umrah pilgrims, as well as to ascertain prospective ‘pilgrims views’ on the marketing strategy implemented by PT. Rizquna Mekkah Madinah. This study uses a descriptive qualitative approach with data collection through semi-structured interviews and direct observation involving marketing staff and prospective pilgrims. The data obtained was analysed through data condensation, data display, drawing and verifying conclusions. The results of the study indicate that the marketing mix strategy implemented has been successful, as evidenced by the availability of various Hajj and Umrah packages, affordable prices in line with the facilities provided, easy access to services through offices, agents, and digital media, as well as active promotional activities through social media and agent networks. In general, prospective pilgrims responded positively because the strategy was considered clear, easy to understand, and in line with their needs. Therefore, it can be concluded that the implementation of an appropriate and integrated marketing mix strategy has a significant impact on increasing the interest and trust of prospective pilgrims in PT. Rizquna Mekkah Madinah.